Diagnostic Performance of Clinical Metagenomic Next-Generation Sequencing for Suspected Central Nervous System Infections in a Municipal Hospital: A Retrospective Study in China - Wang H; Zhao J; Wang X; Li M; Hu T; Xu H; Dong M; He W; Che Z (Infection and Drug Resistance)
Huimin Wang,1– 4,* Jianting Zhao,5,* Xueyao Wang,2 Miaomiao Li,2 Tiantian Hu,2 Huan Xu,6 Min Dong,1 Wenlong He,7 Zhenyong Che5 1Special Need Wards (Department of Neurology and Geriatrics), Xinxiang Central Hospital, Xinxiang, Henan Province, People’s Republic of China; 2Department of Neurology, the Fourth Clinical College of Xinxiang Medical University, Xinxiang, Henan Province, People’s Republic of China; 3Neuromolecular Diagnosis and Transformation Laboratory, Xinxiang Central Hospital, Xinxiang, Henan Province, People’s Republic of China; 4Xinxiang Key Laboratory of Diagnosis, Treatment, and Transformation for Major Neurological Diseases, Xinxiang Central Hospital, Xinxiang, Henan Province, People’s Republic of China; 5Department of Neurology, Xinxiang Central Hospital, Xinxiang, Henan Province, People’sRepublic of China; 6Department of Scientific Affairs, Vision Medicals Center for Infectious Diseases, Guangzhou, Guangdong Province, People’s Republic of China; 7Department of Neurointervention, Xinxiang Central Hospital, Xinxiang Medical University, Xinxiang, Henan Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhenyong Che, Xinxiang Central Hospital, No. 56 Jinsui Avenue, Xinxiang, Henan Province, 453000, People’s Republic of China, Tel/Fax +86 15637359151, Email chezhenyong66@126.com Wenlong He, Department of Neurointervention, Xinxiang Central Hospital, No. 56 Jinsui Avenue, Xinxiang, Henan Province, 453000, People’s Republic of China, Tel/Fax +8615637359288, Email hewl1977@126.comPurpose: Cerebrospinal fluid (CSF) metagenomic next-generation sequencing (mNGS) has the potential to identify the majority of pathogens in a single test. Accurate pathogen identification is vital for central nervous system infection (CNSi). However, there are few related studies investigating in a municipal hospital.Patients and Methods: A total of 52 suspected CNSi patients were retrospectively recruited in Xinxiang central hospital between July 2019 and April 2023. The diagnostic performance of CSF mNGS, conventional microbiological tests (CMT), and the combination of CSF mNGS and CMT were evaluated by comparing to the final diagnosis.Results: Among 52 suspected CNSi patients, 35 were diagnosed as CNSi. In comparison to the final diagnosis, the area under curves (AUC) for CSF CMT, CSF mNGS, and the combination of CMT and mNGS for the diagnosis of CNSi were 0.56 (95% CI 0.4– 0.72), 0.74 (95% CI 0.61– 0.84), and 0.76 (95% CI 0.63– 0.88), respectively. The sensitivities were 11.43% (95% CI 4.54%– 25.95%), 48.57% (95% CI 32.99%– 64.43%), and 51.43% (95% CI 35.57%– 67.01%), respectively. The accuracy was 40.38 (95% CI 27.01%– 54.90%), 65.38% (95% CI 50.91%– 78.03%), and 67.31% (95% CI 52.89%– 79.67%), respectively. Furthermore, based on CSF mNGS results, seven patients confirmed initial treatment, two escalated, and one de-escalated. Additionally, we identified the optimal cutoff values as 1.75 U/L for CSF adenosine deaminase (ADA), 75.44 U/L for CSF protein, and 185 mmH2O for CSF pressure, when these values were exceeded, CSF mNGS tended to yield positive results.Conclusion: CSF mNGS showed superior diagnostic performance in CNSi and hence could serve as a complementary tool to CMT and conjunctively guide the precision therapy. Additionally, the values for CSF ADA, protein and pressure could assist in predicting mNGS positive result. With technical improvements for mNGS sample processing to increase throughput and reduce costs, clinicians may use mNGS more widely in municipal hospital laboratories.Keywords: CNS infections, mNGS, CSF, conventional microbiological tests, CMT